Do YOU know the Ki-67 index of your breast cancer patients? Knowledge of your institution’s Ki-67 index distribution and its robustness is essential for decision-making in early breast cancer - Angela Fischer Maranta; Simon Broder; Constanze Fritzsche; Michael Knauer; Beat Thürlimann; Wolfram Jochum; Thomas Ruhstaller (Breast, 2020)
Objectives: The proliferative activity of the Ki-67 index is important in decision-making of adjuvant treatments in early breast cancer. Its reliability can be reduced by inter-observer variability. This analysis’ objective is to evaluate the robustness of Ki-67 values within one center over 5 years and to compare its distribution with a published dataset. Materials and methods: Ki-67 indices of early breast cancers treated at St. Gallen Breast Center were collected (2010–2014; 1154 patients). Distribution of Ki-67 values was analyzed for each year, along with histologic subtype and grading. Tumors were classified into intrinsic subtypes using two definitions: 2013 St. Gallen Consensus and the refined definition by Maisonneuve (“Milano Group”). Our institution’s Ki-67 cut-off value was adjusted to obtain the same distribution of luminal subtypes as published data of the Milano Group. Results: Ki-67 index frequency distributions were comparable between years (mean 26–30%, median 22–26%). Shape and position of the distribution curves were nearly identical. Ki-67 values correlated with tumor grade (median Ki-67: G1: 12.0%, G2: 21%, G3: 38%). Standard deviation of Ki-67 increased with higher grading (G1: 6.9; G2: 9.2; G3: 18.2; p < 0.001). According to the 2013 definition (and refined definition respectively), there were 35% (41%) luminal A-like and 65% (59%) luminal B-like tumors. To obtain the same distribution as the Milano group, Ki-67 cut-off needed to be elevated to 22%. Conclusions: Ki-67 index assessment was comparable over many years. Knowledge of one’s institution’s Ki-67 value distribution is essential for clinical decision-making of adjuvant therapies in early breast cancer.